A flexible nanofiber membrane containing dendritic oxygen probe for visual monitoring pressure distribution - Wang, Ting; Cai, Shaoyong; Wu, Jianchang; Jiang, Chengwei; Xiao, Ziyu; Akram, Muhammad; Cao, Ge; Tian, Yanqing (Talanta, 2024)
Pressure-sensitive paints (PSP) enable non-intrusive visualization of surface pressure distribution on model surface which is important for aerodynamic studies. However, conventional PSP materials suffer from photobleaching and inadequate sensitivity. In this work, we rationally designed and synthesized novel dendritic oxygen probes (PT1 and PT2) by covalently grafting fluorinated dendrons onto platinum tetrakis(pentafluorophenyl)porphyrin (PT0) (a common oxygen probe). Subsequently, PT2 loaded nanofibers membranes from polycaprolactone (PCL) were fabricated by electrospinning. Fabricated membranes showed high oxygen sensitivity (I0/I100 = 35.3) with excellent flexibility, good reversibility, and outstanding photostability (merely 2.0% intensity loss after prolonged irradiation). The pressure sensitivity was found around 0.73 % per kilopascal. Furthermore, significant variation in emission intensity with respect to the variation in air pressure (1.3–101.32 kPa), facilitates the naked eye visualization of the pressure distribution on the membrane surface. Such excellent oxygen and pressure sensitivity and photostability might be due to high fluorine contents of complex dendritic structure of PT2. This flexible fluorine-functionalized dendritic oxygen probe puts forward a facile and effective strategy to develop advanced PSP materials enabling accurate pressure mapping for aerodynamic studies.
CRIS-Team Scopus Importer:2024-05-10
Keywords: Dendritic copolymer; Fluorine; Oxygen sensitivity; Platinum porphyrin; Pressure-sensitive paints

An Automated Workflow to Discover the Structure-Stability Relations for Radiation Hard Molecular Semiconductors - Bornschlegl, Andreas; Duchstein, Patrick; Wu, Jianchang; Rocha-Ortiz, Juan S.; Caicedo-Reina, Mauricio; Ortiz, Alejandro; Insuasty, Braulio; Zahn, Dirk; Lüer, Larry; Brabec, Christoph (Journal of the American Chemical Society, 2025)
Emerging photovoltaics for outer space applications are one of the many examples where radiation hard molecular semiconductors are essential. However, due to a lack of general design principles, their resilience against extra-terrestrial high-energy radiation can currently not be predicted. In this work, the discovery of radiation hard materials is accelerated by combining the strengths of high-throughput, lab automation and machine learning. This way, a large material library of more than 130 organic hole transport materials is automatically processed, degraded, and measured. The materials are degraded under ultraviolet-C (UVC) light in a nitrogen atmosphere, serving as the conditions for electromagnetic radiation hardness tests. A value closely related to the differential quantum yield for photodegradation is extracted from the evolution of the UV-visible (UV-vis) spectra over time and used as a stability target. Following this procedure, a stability ranking spanning over 3 orders of magnitude was obtained. Combining Gaussian Process Regression based on predictors from structural fingerprints and manual filtering of the materials by features, structure-stability relations for UVC stable materials could be found: Fused aromatic ring clusters are beneficial, whereas thiophene, methoxy and vinylene groups are detrimental. Comparing the UV-vis spectra of the degraded material in film and solution, bond cleavage could be made out as the leading degradation mechanism. Even though UVC light can in principle break most organic bonds, the stable materials are able to distribute and dissipate the energy well enough so that the chemical structures remain stable. The established predictive model quantifies the effect of specific molecular features on UVC stability, allowing chemists to consider UVC stability in their molecular design strategy. In the future, a larger data set will allow to inversely design molecular semiconductors which show high performance and radiation hardness at the same time.
CRIS-Team Scopus Importer:2025-01-31

Controlling Intermediate Phase Formation to Enhance Photovoltaic Performance of Inverted FA-Based Perovskite Solar Cells - Li, Chaohui; Park, Hyoungwon; Qiu, Shudi; Streller, Fabian; Zhang, Kaicheng; Peng, Zijian; Byun, Jiwon; Tian, Jingjing; Maiti, Santanu; Xie, Zhiqiang; Dong, Lirong; Liu, Chao; et al. (ACS Energy Letters, 2024)
Formamidinium (FA)-based perovskites exhibit significant potential for highly efficient photovoltaics due to their promising optoelectronic properties and optimal bandgap. However, the undesired inactive phase arises from multiple crystal nucleation pathways formed by various intermediate phases during the film formation process, persistently accompanying it. FA-based perovskites frequently struggle to form uniform, highly crystalline films. This challenge complicates the development of reliable and highly reproducible crystallization processes for perovskites and the establishment of guidelines for controlling the α-phase formation. In this work, we investigate the role of poly(acrylonitril-co-methyl acrylate) (PAM) to simultaneously control nucleation and subsequent α-phase crystallization. This successfully demonstrates the regulation of oriented crystal growth through the creation of a PAM-PbI2 intermediate. Ultimately, PAM-modified p-i-n architecture devices obtain a promising power conversion efficiency (PCE) of 25.30%, with VOC (1.211 V), achieving 95% of the detailed balance limit. Additionally, PAM-modified devices maintain ≥90% of the initial efficiency for 1000 h under 1 sun and 65 °C operation.
CRIS-Team Scopus Importer:2024-11-22

Correction to: Polymer-acid-metal quasi-ohmic contact for stable perovskite solar cells beyond a 20,000-hour extrapolated lifetime (Nature Communications, (2024), 15, 1, (2002), 10.1038/s41467-024-46145-7) - Luo, Junsheng; Liu, Bowen; Yin, Haomiao; Zhou, Xin; Wu, Mingjian; Shi, Hongyang; Zhang, Jiyun; Elia, Jack; Zhang, Kaicheng; Wu, Jianchang; Xie, Zhiqiang; Liu, Chao; et al. (Nature Communications, 2024)
Correction to: Nature Communicationshttps://doi.org/10.1038/s41467-024-46145-7, published online 05 March 2024 In this article, Junsheng Luo and Bowen Liu should have been denoted as equally contributing authors. The original article has been corrected.
CRIS-Team Scopus Importer:2024-05-17

Enhancing Planar Inverted Perovskite Solar Cells with Innovative Dumbbell-Shaped HTMs: A Study of Hexabenzocoronene and Pyrene-BODIPY-Triarylamine Derivatives - Rocha-Ortiz, Juan S.; Wu, Jianchang; Wenzel, Jonas; Bornschlegl, Andreas; Perea, Jose Dario; Leon, Salvador; Barabash, Anastasia; Wollny, Anna-Sophie; Guldi, Dirk Michael; Zhang, Jiyun; Insuasty, Alberto; Lüer, Larry; et al. (Advanced Functional Materials, 2023)
Keywords: hexabenzocoronene; donor–acceptor; BODIPY; π-conjugation; perovskite solar cells; hole-transport materials

Exploring the Steric Hindrance of Alkylammonium Cations in the Structural Reconfiguration of Quasi-2D Perovskite Materials Using a High-throughput Experimental Platform - Zhang, Jiyun; Wu, Jianchang; Langner, Stefan; Zhao, Baolin; Xie, Zhiqiang; Hauch, Jens; Afify, Hany A.; Barabash, Anastasia; Luo, Junsheng; Sytnyk, Mykhailo; Meng, Wei; Zhang, Kaicheng; et al. (Advanced Functional Materials, 2022)
Reduced-dimensional (2D or quasi-2D) perovskites have recently attracted considerable interest due to their superior long-term stability. The nature of the intercalating cations plays a key role in determining the physicochemical properties and stability of the quasi-2D perovskites. Here, the thermal stability of a series of 2D Ruddlesden−Popper (RP) perovskites is studied using seven types of intercalating cations with increasing linear carbon-chain length from ethylammonium (EA) to n-dodecylammonium (DA) through a high-throughput platform. The results show that long-chain cations in quasi-2D perovskite films lead to strong steric hindrance between adjacent perovskite domains, thus suppressing Ostwald ripening during the thermal-aging process. For short-chain cations, increased-dimensional phase redistribution during the aging period is observed, which can benefit a concomitant regeneration of the 3D/3D-like perovskite phases. The impact of steric hindrance on structural reconfiguration and the subsequent phase redistribution in quasi-2D perovskites are systematically characterized by UV–vis absorption spectra, photoluminescence spectra, and X-ray diffraction patterns. Due to the steric hindrance effect, an optimal chain length is found to maximize film stability by balancing the water/oxygen resistance and increased-dimensional phase redistribution. This work provides new insight into the thermal stability of quasi-2D perovskites.
CRIS-Team Scopus Importer:2022-09-02
Keywords: 2D perovskite materials; high-throughput platform; stability performance; steric hindrance; steric structure and reconfiguration

Highly Stable n–i–p Structured Formamidinium Tin Triiodide Solar Cells through the Stabilization of Surface Sn2+ Cations - Hu, Manman; Risqi, Andi Muhammad; Wu, Jianchang; Chen, Liang; Park, Jaewang; Lee, Seung Un; Yun, Hyun Sung; Park, Byung Wook; Brabec, Christoph; Seok, Sang Il (Advanced Functional Materials, 2023)
Improving the performance, reproducibility, and stability of Sn-based perovskite solar cells (PSCs) with n–i–p structures is an important challenge. Spiro-OMeTAD [2,2′,7,7′-tetrakis(N,N-di-p-methoxyphenyl-amine)9,9′-spirobifluorene], a hole transporting material (HTM) with n–i–p structure, requires the oxygen exposure after addition of Li-TFSI [Lithium bis(trifluoromethanesulfonyl)imide] as a dopant to increase the hole concentration. In Sn-based PSC, Sn2+ is easily oxidized to Sn4+ under such a condition, resulting in a sharp decrease in efficiency. Herein, a formamidinium tin triiodide (FASnI3)-based PSCs fabricated using DPI-TPFB [4-Isopropyl-4′-methyldiphenyliodonium tetrakis(pentafluorophenyl)borate] instead of Li-TFSI are reported as a dopant in Spiro-OMeTAD. The DPI-TPFB enables the fabrication of PSCs with an efficiency of up to 10.9%, the highest among FASnI3-based PSCs with n–i–p structures. Moreover, ≈80% of the initial efficiency is maintained even after 1,597 h under maximum power point tracking conditions. In particular, the encapsulated device does not show any decrease in efficiency even after holding for 50 h in the 85 °C/85% RH condition. The high efficiency and excellent stability of PSCs prepared by doping with DPI-TPFB are attributed to not only increasing electrical conductivity by acting as a Lewis acid, but also stabilizing Sn2+ through coordination with Sn2+ on the surface of FASnI3.
CRIS-Team Scopus Importer:2023-04-21
Keywords: efficiency; new dopants; n–i–p structure; oxidation; pure tin perovskite; Spiro-OMeTAD; stability

Integrated System Built for Small-Molecule Semiconductors via High-Throughput Approaches - Wu, Jianchang; Zhang, Jiyun; Hu, Manman; Reiser, Patrick; Torresi, Luca; Friederich, Pascal; Lahn, Leopold; Kasian, Olga; Guldi, Dirk Michael; Perez-Ojeda Rodriguez, Maria Eugenia; Barabash, Anastasia; Rocha Ortiz, Juan Sebastian; et al. (Journal of the American Chemical Society, 2023)
High-throughput synthesis of solution-processable structurally variable small-molecule semiconductors is both an opportunity and a challenge. A large number of diverse molecules provide a possibility for quick material discovery and machine learning based on experimental data. However, the diversity of the molecular structure leads to the complexity of molecular properties, such as solubility, polarity, and crystallinity, which poses great challenges to solution processing and purification. Here, we first report an integrated system for the high-throughput synthesis, purification, and characterization of molecules with a large variety. Based on the principle “Like dissolves like,” we combine theoretical calculations and a robotic platform to accelerate the purification of those molecules. With this platform, a material library containing 125 molecules and their optical-electronic properties was built within a timeframe of weeks. More importantly, the high repeatability of recrystallization we design is a reliable approach to further upgrading and industrial production.<br

Intercalating-Organic-Cation-Induced Stability Bowing in Quasi-2D Metal-Halide Perovskites - Zhang, Jiyun; Langner, Stefan; Wu, Jianchang; Kupfer, Christian; Lüer, Larry; Meng, Wei; Zhao, Baolin; Liu, Chao; Daum, Manuel; Osvet, Andres; Li, Ning; Halik, Marcus; et al. (ACS Energy Letters, 2022)
Quasi-2D metal-halide perovskites with Ruddlesden-Popper structures have shown promising stability due to the protective effects of the intercalating organic cations. However, a systematic study of the effect of intercalating organic cations on stability has rarely been reported. Here we use a high-throughput-robot platform to fabricate over 300 perovskite films and study the effect of cations and their concentrations on the thermal stability of perovskite films. We find that approximately 20-25 mol % of intercalating organic cations into MAPbI3 (nominal n = 4/5) can maximize the film stability, while higher/lower concentrations lead to inferior stability, which is termed stability bowing in analogy to band-gap bowing. A model with two competitive effects of the intercalating organic cation (better protection vs more defects) is proposed to rationalize this behavior. We anticipate this work to provide new insights into the stability of quasi-2D perovskites.
CRIS-Team Scopus Importer:2022-02-11

Optimizing Perovskite Thin-Film Parameter Spaces with Machine Learning-Guided Robotic Platform for High-Performance Perovskite Solar Cells - Zhang, Jiyun; Liu, Bowen; Liu, Ziyi; Wu, Jianchang; Arnold, Simon; Shi, Hongyang; Osterrieder, Tobias; Hauch, Jens; Wu, Zhenni; Luo, Junsheng; Wagner, Jerrit; Berger, Christian; et al. (Advanced Energy Materials, 2023)
Simultaneously optimizing the processing parameters of functional thin films remains a challenge. The design and utilization of a fully automated platform called SPINBOT is presented for the engineering of solution-processed functional thin films. The SPINBOT is capable of performing experiments with high sampling variability through the unsupervised processing of hundreds of substrates with exceptional experimental control. Through the iterative optimization process enabled by the Bayesian optimization (BO) algorithm, the SPINBOT explores an intricate parameter space, continuously improving the quality and reproducibility of the produced thin films. This machine learning (ML)-guided reliable SPINBOT platform enables the acceleration of the optimization process of perovskite solar cells via a simple photoluminescence characterization of films. As a result, this study arrives at an optimal film that, when processed into a solar cell in an ambient atmosphere, immediately yields a champion power conversion efficiency (PCE) of 21.6% with satisfactory performance reproducibility. The unsealed devices retain 90% of their initial efficiency after 1100 h of continuous operation at 60–65 °C under metal-halide lamps. It is anticipated that the integration of robotic platforms with the intelligent algorithm will facilitate the widespread adoption of effective autonomous experimentation to address the evolving needs and constraints within the materials science research community.
CRIS-Team Scopus Importer:2023-11-10
Keywords: closed-loop optimization; efficient and stable devices; machine learning; manufacturing optimization; perovskite thin films; PL characterization; robotic platform

Polymer-acid-metal quasi-ohmic contact for stable perovskite solar cells beyond a 20,000-hour extrapolated lifetime - Luo, Junsheng; Liu, Bowen; Yin, Haomiao; Zhou, Xin; Wu, Mingjian; Shi, Hongyang; Zhang, Jiyun; Elia, Jack; Zhang, Kaicheng; Wu, Jianchang; Xie, Zhiqiang; Liu, Chao; et al. (Nature Communications, 2024)
The development of a robust quasi-ohmic contact with minimal resistance, good stability and cost-effectiveness is crucial for perovskite solar cells. We introduce a generic approach featuring a Lewis-acid layer sandwiched between dopant-free semicrystalline polymer and metal electrode in perovskite solar cells, resulting in an ideal quasi-ohmic contact even at elevated temperature up to 85 °C. The solubility of Lewis acid in alcohol facilitates nondestructive solution processing on top of polymer, which boosts hole injection from polymer into metal by two orders of magnitude. By integrating the polymer-acid-metal structure into solar cells, devices exhibit remarkable resilience, retaining 96% ± 3%, 96% ± 2% and 75% ± 7% of their initial efficiencies after continuous operation in nitrogen at 35 °C for 2212 h, 55 °C for 1650 h and 85 °C for 937 h, respectively. Leveraging the Arrhenius relation, we project an impressive T80 lifetime of 26,126 h at 30 °C.
CRIS-Team Scopus Importer:2024-03-15

Precise control of process parameters for >23% efficiency perovskite solar cells in ambient air using an automated device acceleration platform - Zhang, Jiyun; Wu, Jianchang; Barabash, Anastasia; Du, Tian; Qiu, Shudi; Le Corre, Vincent Marc; Zhao, Yicheng; Zhang, Kaicheng; Schmitt, Frederik; Peng, Zijian; Tian, Jingjing; Li, Chaohui; et al. (Energy and Environmental Science, 2024)
Achieving high-performance perovskite photovoltaics, especially in ambient air, is critically dependent on the precise optimization of process parameters. However, traditional manual methods often struggle to effectively control the key variables. This inherent challenge requires a paradigm shift toward automated platforms capable of precise and reproducible experiments. Herein, we use a fully automated device acceleration platform (DAP) to optimize air-processed parameters for preparing perovskite devices using a two-step sequential deposition technique. Over ten process parameters with significant potential to influence device performance are systematically optimized. Specifically, we delve into the impact of the dripping speed of organic ammonium halide, a parameter that is difficult to control manually, on both perovskite film and device performance. Through the targeted design of experiments, we reveal that the dripping speed significantly affects device performance primarily by adjusting the residual PbI2 content in the films. We find that optimal dripping speeds, such as 50 µL s−1, contribute to top-performance devices. Conversely, excessively fast or slow speeds result in devices with comparatively poorer performance and lower reproducibility. The optimized parameter set enables us to establish a standard operation procedure (SOP) for additive-free perovskite processing in ambient conditions, which yield devices with efficiencies surpassing 23%, satisfactory reproducibility, and state-of-the-art photo-thermal stability. This research underscores the importance of understanding the causality of process parameters in enhancing perovskite photovoltaic performance. Furthermore, our study highlights the pivotal role of automated platforms in discovering innovative workflows and accelerating the development of high-performing perovskite photovoltaic technologies.
CRIS-Team Scopus Importer:2024-07-19

Regulating the Surface Passivation and Residual Strain in Pure Tin Perovskite Films - Hu, Manman; Nie, Riming; Kim, Hyeonwoo; Wu, Jianchang; Chen, Shanshan; Park, Byung-Wook; Kim, Gwisu; Kwon, Hyoung-Woo; Seok, Sang Il (ACS Energy Letters, 2021)
The passivation of electronic defects at the surfaces and grain boundaries of perovskite materials is one of the most important strategies for suppressing charge recombination in perovskite solar cells (PSCs). Although several passivation molecules have been investigated, few studies have focused on their application in regulating both the surface passivation and residual strain of perovskite films. In this study, the residual strain distribution profiles of the Cs0.1FA0.9SnI3 perovskite thin films and their effect on the photovoltaic device efficiencies were investigated. We found a gradient distribution of the out-of-plane compressive strain that correlated with the compositional inhomogeneity perpendicular to the substrate surface. By deliberately engineering dual effects of the surface passivation and residual strain, we achieved a record power conversion efficiency of up to 9.06%, the highest ever reported in a typical n-i-p architecture.
CRIS-Team Scopus Importer:2021-11-05

Revealing the Crystallization and Thermal-Induced Phase Evolution in Aromatic-Based Quasi-2D Perovskites Using a Robot-Based Platform - Zhang, Jiyun; Wu, Jianchang; Zhao, Yicheng; Zou, Yuqin; Barabash, Anastasia; Wu, Zhenni; Zhang, Kaicheng; Deng, Can; Elia, Jack; Li, Chaohui; Rocha Ortiz, Juan Sebastian; Liu, Chao; et al. (ACS Energy Letters, 2023)
Introducing large organic cations to form reduced-dimensional (quasi-2D) perovskites has proven to be effective in stabilizing three-dimensional perovskites. In this study, we synthesized 28 Ruddlesden-Popper-type quasi-2D perovskites using four aromatic-based cations (phenylmethylammonium (PMA), phenethylammonium (PEA), phenylpropylammonium (PPA), and phenylbutanammonium (PBA)) and systematically investigated their optoelectronic and structural properties and thermal stability. A counterintuitive finding that longer-chain PPA-based films exhibited relatively poorer stability compared to films with shorter-chain cations has been found. This instability in PPA-based samples is attributed to significant lattice distortion and a mismatched phase between face-sharing trimers, causing intense configurational strain. On the other hand, PBA-containing films maintained robust structural stability due to distinctive crystallization kinetics and a gradual phase-transformation process (from larger-n to lower-n phases) induced by a stronger steric-hindrance effect. Our study sheds light on the complex impact of aromatic-based cations on optoelectronic properties and stability of perovskites, providing guidelines for the rational compositional design engineering of highly stable perovskite material

Unraveling Dual Operational Mechanisms in an Air-Stable All Inorganic Perovskite for Nonvolatile Memory and Neuromorphic Computing - Xie, Zhiqiang; Zhang, Difei; Cheng, Long; Li, Chaohui; Elia, Jack; Wu, Jianchang; Tian, Jingjing; Chen, Lijun; Loi, Maria Antonietta; Osvet, Andres; Brabec, Christoph (ACS Energy Letters, 2024)
Two-terminal drift memristors (nonvolatile) are widely employed to emulate biological synaptic functionalities in neuromorphic architectures. However, reliable emulations of synaptic dynamics can only be achieved through the integration of their counterparts, diffusive memristors. Moreover, the combination of drift and diffusive memristors represents a desirable approach to address the escalating demands posed by the increasing complexity of neuromorphic computing frameworks, which are still in their nascent stages. Accordingly, an air-stable inorganic perovskite memristor (RbPbI3) is demonstrated with adjustable drift and diffusive modes. By employing an electroforming process, the drift-type devices demonstrate bipolar resistive switching with a large ON/OFF ratio (102), stable endurance (2000 cycles), long retention (1.2 × 105 s), and robust air stability. In contrast, diffusive-type devices, without an electroforming process, effectively emulate synaptic behaviors, including paired-pulse facilitation, long-term potentiation/depression, and spike-timing-dependent plasticity. Additionally, experimental data are utilized to train neural networks constructed with perovskite artificial synapses on image classification tasks. The results demonstrate accuracies of 89.24% (MNIST) and 79.10% (Fashion-MNIST) under supervised learning, closely approximating their theoretical values.
CRIS-Team Scopus Importer:2024-03-01